(untitled) (Universal International Scientific Journal, 2026)
This study investigated the pedagogical potential of national music in the formation of students’ spiritual and moral immunity. The methods of theoretical analysis, pedagogical observation and comparison were used during the study. The results showed that aesthetic taste, moral values ​​and patriotic feelings are effectively developed in students through national music. According to the conclusions of the study, national music is an important means of spiritual education in the higher education system.